Medieval Birmingham : people and places, 1070-1553 - Hemingway, John, (Archaeopress Archaeology, 2022)
'Medieval Birmingham' attempts to show through documentary and archaeological evidence how it evolved from a village into its present role as the second city of the United Kingdom. It looks at the lives of the Bermingham family, who owned the town and ruled the townsmen. It looks at their retinue, who held surrounding manors in the area. It tells of the various wars both served in - civil and overseas. The medieval period was a time when the Christian church had great power, and its role in the manor is told, examining the canons of the priory, the friars and the parish priests. Probably the most important element were the inhabitants of the town, for it was they that built it up through trade, and their lives, occupations and physical surroundings form the final section of the book.